Trauma Perang Salib dalam Hubungan Islam-Barat - Mohammad Affan (Jurnal Sosiologi Reflektif, 2014)
The Crusade taking place during two centuries (10951291 AD) was the beginning of largescale confrontation between Islam and Western Christianity. Although the Crusades ended eight centuries ago, but it still lingers in the mind of Western Christians and some Muslims. The subsequent conflcts between both sides have been always linked to the Crusades. For example, colonialism and imprealism of Western to the East during the 18th, 19th, and 20th century is considered as a continuation of the Crusades. In addition, the war against terrorism that the United States campaigned for the post September 11, 2001 propagated as the 2nd Crusades. Similarly, the invasion of the United States and its allies against Iraq and Afghanistan is refering the arrogances of West against Islam. These facts indicate that a huge trauma caused by the Crusades still entrenched in the minds of most of the psychohistorical Western and Muslim. Therefore, to promote a harmonious relationship between the West and Islam, the perceptions and negative images of Islam in the eyes of the West and vice versa, should be neutralized. The history has proven that when peace and truce conducted during the period of the Crusades, both parties could work together in trade and economy. In the current global context, the cooperation must be expanded. Through good cooperation and mutual benefi, suspicion and prejudice to each other will eventually fade.